Basic thermodynamic and dynamic characteristics of the glass forming intermetallics - Ji Wang; Zhengqing Cai; Heng Kang; Benke Huo; Yanhui Zhang; Yanqin Gao; Zijing Li; Shidong Feng; Li-min Wang (Materials & Design, 2024)
Recent studies on intermetallic glasses challenged the conventional cognition that the glass formability would be deteriorated by the presence of intermetallics. To reveal the vitrification mechanism of intermetallics, three binary metallic alloys with multiple intermetallics and wide glass forming region are focused. The thermodynamics and dynamics of the intermetallics are studied by combining experiments and simulations, revealing that the glass forming systems can be featured by low melting entropy, low diffusion coefficient, and low formation enthalpy. Close inspection emphasizes the critical influence of the melting entropy in glass formation of intermetallics, and intermetallics with low melting entropy are of enhanced glass formability. In addition, for the glass forming intermetallics, the melting entropy shows close connection to the dynamics such as diffusion coefficients or viscosity of the liquids at melting temperature, with which a basic reference to design metallic glasses is substantiated.